Towards inclusion and diversity in the light of Universal Design: three administrative buildings in Aswan city as case studies - M. E. Khalil (SpringerOpen, 2021)
Abstract Social inclusion aims to achieve an inclusive society that entails respect for human diversity and upholds principles of equality and equity, allowing all groups to take part in the society. Universal Design (UD) promotes inclusiveness by supporting access for all and easy use of the built environment, thus eliminating any form of exclusion and discrimination. This study examines the UD application in Aswan’s administrative buildings. The study relied on the descriptive, analytical, and inductive approach, through the identification of deficiencies in the selected administrative buildings’ design, and the clarification of development strategies to make these buildings for all. The case study method has two processes (approaches) in evaluating the case study buildings; the first was by the researchers according to UD requirements using the study’s checklist; the second was by users according to UD principles using interviews and task sheets. This research aims at emphasizing the positive effects of UD application on the selected buildings. In addition, it also aims at determining the compatibility of those buildings with the UD concept. The study result showed that the case study buildings are not compatible considerably with the requirements of the UD and its principles. The research concluded that architects should consider UD requirements and principles when designing administrative buildings and when rehabilitating and developing the existing ones. Thus, the study’s outputs could be used as a guidance tool by architects and construction managers in introducing universally designed buildings to all users.